PERFORMANSI MORFOLOGI BIBIT KELAPA SAWIT (ELAEIS QUINEENSIS JACQ) DI PRE NURSEY PADA APLIKASI SP-36 DAN UREA - Agnes I. Manurung; Petralius Hulu; Bilter Sirait (Jurnal Darma Agung, 2022)
Background and Objective: The role of phosphorus and nitrogen is very important for the metabolism of oil palm plants in the nursery phase. This study aims to determine the morphophysiological performance of oil palm (Elaeis quineensis Jacq) seedlings in the pre-nursery due to the application of SP-36 fertilizer and urea. Materials and Methods:The research was conducted on Jln. Bunga Ncole Permai, No.30 Medan Tuntungan District with an altitude of ± 20 meters above sea level. This research is done June 2021 to August 2021. The study used a factorial Randomized Block Design with two factors. The first factor is the dose of SP-36 fertilizer with 3 levels of S1 = 5 g/polybag; S2 = 10g/polybag; S3 = 15 g/polybag. The second factor is the dose of urea fertilizer with 3 levels: U1 = 3 g/polybag, U2 = 5 g/polybag and U3 = 7 g/polybag. Results: The results showed that the dose of SP-36 fertilizer had a significant effect on stem diameter at 12 WAP, number of leaves at 8, 10 and 12 WAP, and leaf length at 10 and 12 WAP. The urea dose treatment significantly affected plant height at 6, 8, 10, and 12 WAP, stem diameter at 10 and 12 WAP, number of leaves at 6, 8, 10 and 12 WAP, and leaf length at 8, 10 and 12 WAP. The interaction between the two treatments did not have a significant effect on all ages of observation. Conclusions: the best oil palm seedling growth was found in the treatment of SP-36 S3 fertilizer dosage = 15 g/polybag and urea 7g/polybag.